An Increasing Relationship Strength Between India and Afghanistan: Implications of the India-Afghanistan Strategic Partnership (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The India-Afghanistan Strategic Partnership signed onOctober 04, 2011 was the first agreement that Afghanistanhas formally entered into with any country to reconstruct Afghanistan, help guarantee its security and islinked with the drawdown of US forces from Afghanistan. Afghanistan views thestrong ties with India as a means to assuage the sense of insecurity and capableof assisting the war-torn nation to stabilize the helpless nation on account ofthe debilitating power struggle anticipated in the power vacuum following thewithdrawal in 2014 of the US and NATO forces. Pakistanis concern about the agreement and is quite suspicious of encirclement by India.